Augmented Reality Book Sistem Rumah Tradisional Bali Berdasarkan Asta Kosala-Kosali - Endra Wiartika P, I Made; Nyoman C, Padma; Mahendra Darmawiguna, I Gede; Windu Antara Kesiman, Made (Universitas Pendidikan Ganesha, 2013)
The times brought changes the existence of homesin Bali under the influence of the external architecture. AstaKosala-Kosali is ordinance, layout, and urban design forresidential buildings in Bali which accordance with thephilosophical foundation, ethical, and ritual has begun to beforgotten by Balinesse people. Destination of the research is thedevelopment of applications that can be used as media forlearning, introduce and preserve the concept of a traditionalBalinese house system based Asta Kosala-Kosali. The researchmethod used is a research and development, to develop anAugmented Reality Book application of traditional Balinesehouse system based Asta Kosala-Kosali. Augmented Reality Bookusing the library vuforia able to incorporate a virtual object intoa real environment the help of books and android smartphonedisplaying 3D objects on the concept of traditional Balinesebuildings based Asta Kosala-Kosali and playing a soundnarrative explanation, so it is easier to observe and interact withthe objects that appear. Results of the research is thedevelopment a book and system of traditional Balinese houseapplications based on android that can be solution to facilitateand provide a new experience in learning the concept of AstaKosala-Kosali. So Balinesse people understand when makinghouse in Bali rooted in the concept of Asta Kosala-Kosali arebased on a balance or harmony (Tri Hita Karana).